Slower recovery rate of muscle oxygenation after sprint exercise in long-distance runners compared with that in sprinters and healthy controls - Nagasawa, T. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to examine whether differences in aerobic capacity and training status influence muscle reoxygenation after sprint exercise. We hypothesized that the muscle reoxygenation rate after sprint exercise is slower in long-distance runners with a high aerobic capacity. Five male long-distance runners, 5 male sprinters, and 6 healthy male controls performed a 30-second sprint exercise on a cycle ergometer. Oxygen saturation in muscle tissue (StO2) in the vastus lateralis muscles was measured by near-infrared spectroscopy. The muscle reoxygenation rate after the exercise was evaluated at half the time required for StO2 recovery (T1/2 StO2). Aerobic capacity was evaluated by measuring maximal oxygen consumption (VO2max). The T1/2 StO2 in the long-distance runners (25.0 ± 4.5 seconds) was significantly longer than that in the controls (15.9 ± 1.6 seconds; p < 0.01) and in the sprinters (18.0 ± 4.6 seconds; p < 0.05). In all the subjects (long-distance runners, sprinters, and controls), the T1/2 StO2 had a significant positive correlation with the VO2max (r = 0.75; p < 0.01) and was longer in subjects with a higher VO2max. These results suggest that reoxygenation after sprint exercise is influenced by aerobic capacity and training status, and that the subjects with a higher aerobic capacity have delayed muscle reoxygenation after sprint exercise.